2016
DOI: 10.1590/0366-69132016623621934
|View full text |Cite
|
Sign up to set email alerts
|

Obtenção de espumas cerâmicas a partir de resíduo da terra diatomácea e ignimbrita pelo método de réplica

Abstract: ResumoAs cerâmicas celulares são materiais frágeis de elevada porosidade e área superficial. O grande interesse por esta classe de materiais está relacionado às suas propriedades específicas e a sua permeabilidade com substâncias líquidas e gasosas. O objetivo principal deste trabalho foi desenvolver um suporte cerâmico poroso a partir de resíduo da terra diatomácea e ignimbrita pelo método de réplica a fim de atenuar os poluentes emitidos pela queima de tijolos e telhas provenientes da indústria da cerâmica v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Table VIII lists the chemical compositions of various inorganic industrial wastes used as alternative raw materials in the production of porous ceramics. Among them, those from the brewing [33,34], ornamental rocks [35][36][37], ceramic [35,[38][39][40][41][42], metallurgical [43,44] and mining [45][46][47][48][49] industries, thermal power plants [96][97][98] and others [13,50,51,99] stand out. It is observed that the vast majority of these wastes are mainly composed of SiO 2 , that is, they can be used satisfactorily as sources of silica in ceramic technology.…”
Section: Inorganic Wastementioning
confidence: 99%
See 3 more Smart Citations
“…Table VIII lists the chemical compositions of various inorganic industrial wastes used as alternative raw materials in the production of porous ceramics. Among them, those from the brewing [33,34], ornamental rocks [35][36][37], ceramic [35,[38][39][40][41][42], metallurgical [43,44] and mining [45][46][47][48][49] industries, thermal power plants [96][97][98] and others [13,50,51,99] stand out. It is observed that the vast majority of these wastes are mainly composed of SiO 2 , that is, they can be used satisfactorily as sources of silica in ceramic technology.…”
Section: Inorganic Wastementioning
confidence: 99%
“…When diatoms die, their silica shells accumulate on the sea floor and thick layers of these shells are fossilized into diatomaceous earth or diatomite [101,[104][105][106]. Diatomaceous earth, a fine-grained material with a porous structure, is rich in hydrated amorphous silica and has low thermal conductivity, high melting point, high surface area, and low density, in addition to being essentially inert to most chemical liquids and gases [33,106] Table VIII -Chemical composition of inorganic industrial wastes used in the production of porous ceramics.…”
Section: Inorganic Wastementioning
confidence: 99%
See 2 more Smart Citations
“…This consists of impregnation of a polymeric sponge with a ceramic slip, followed by thermal treatment for the calcination of the organic material. Further, these filters are sintered, resulting in a ceramic body that is a replica of the precursor sponge used for the impregnation [12,13].…”
Section: Development Of Nickel and Silver Ceramic Filters Supported On K10 Montmorillonite Clay For Water Disinfection (Desenvolvimento Dmentioning
confidence: 99%